England and Scotland in the fourteenth century new perspectives - King, Andy 1963-; Penman, Michael A. (Boydell & Brewer, 2007)
Were the English and the Scots always at loggerheads in the fourteenth century? The essays here offer a more nuanced picture. Typical accounts of Anglo-Scottish relations over the whole fourteenth century tends to present a sustained period of bitter enmity, described routinely by stock-phrases such as 'endemic warfare', and typified by battles such as Bannockburn [1314], Neville's cross [1346] or Otterburn [1388], border-raiding and the capture of James I of Scotland by English pirates in 1406. However, as this collection shows, the situation was far more complex. Drawing together new perspectives from new and leading researchers, the essays investigate the great complexity of Anglo-Scottish tensions in this most momentous of centuries and in doing so often reveal a far more ambivalent and at times even a peaceful and productive Anglo-Scottish dynamic. The topics treated include military campaigns and ethos; the development of artillery; the leading 'Disinherited' Anglo-Scot, Edward Balliol; Scots in English allegiance and Border Society; religious patronage; Papal relations; the effect of dealings with Scotland on England's government and parliament; identity, ethnicity and otherness; and shared values and acculturation. Contributors: AMANDA BEAM, MICHAEL BROWN, DAVID CALDWELL, GWILYM DODD, ANTHONY GOODMAN, ANDY KING, SARAH LAYFIELD, IAIN MACINNES, RICHARD ORAM, MICHAEL PENMAN, ANDREA RUDDICK AND DAVID SIMPKIN.